Disconnections and exclusions of parents in the prevention of teenage pregnancy: A phenomenological approach - Malebo Tryphina Skosana; Mmapheko Doriccah Peu; Ramadimetja Shirley Mogale (Elsevier, 2020)
Teenage pregnancy is associated with poor maternal outcomes, as well as limited school attendance, which may have future financial implications for the family. This article explores and describes the disconnections and exclusions of parents in the prevention of teenage pregnancy. We conducted a qualitative descriptive phenomenological study, purposively selecting and interviewing 20 parents of both boys and girls. After individually interviewing parents, we analysed the data using the Colaizzi method. Three overarching themes emerged from the interviews, namely, the effects of teenage pregnancy on parents, the prevention strategies and the role of parents in the prevention of teenage pregnancy. Parents emphasised the emotions of love and caring, frustration, exploitation, anger and helplessness. Parents agreed that they should be actively involved in communicating with their teenagers on sex education. They recommended that affordable and accessible youth-friendly services be provided.